POLA INTERAKSI MASYARAKAT PLURAL AGAMA DI KELURAHAN SEI GOHONG KECAMATAN BUKIT BATU KOTA PALANGKA RAYA PROVINSI KALIMANTAN TENGAH - Josef Dudi (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
All social activities occur in relationships and interactions. There are four religions that live side by side and exude amid differences in Sei Gohong, namely Islam, Protestantism, Kaharingan, and Catholicism. The four religions are embraced by people who come from one ethnic Dayak ethnic. The study was analyzed using the theory of social interaction, plurality of religions, conflict theory, social change, social action, symbolic interaction, and social construction. Research using grounded method. The results of this research are: first, there is interaction pattern in the form of cooperation as in dayak customary activity, the accommodation of socialization and economic activities in Sei Gohong, the three patterns of interaction in the form of assimilation, ie, mixed marriages of Sei Gohong residents with Dayak residents or mixed marriages of different religions of Sei Gohon., Fourth, the pattern of interaction in the form of competition and conflict between religious differences. Factors inhibiting the social interactions of plural communities religion in Sei Gohong that is, cultural change, amputation of kademangan institution and mentality betang as institution of plurality begin to retreat. The conclusion of this study that different religions is not a barrier to spontaneous social mechanisms and harmony of life in Sei Gohong.